STUDY OF A NEW METHOD FOR THE REMAINING LIFE PREDICTION OF CORROSION PIPELINE - JIANG Feng; ZHENG YunHu (Jixie qiangdu)
For the reliability problems of large data samples and low prediction accuracy and statistics to predict the remaining life of the corrosion pipelines,the author proposed the gray prediction theory to predict the residual life of corrosion pipelines; For the problem of unable to do with non-isochronous data、larger errors in the process of background values construction and had not used new information fully of the traditional GM（ 1,1） model,the author optimized the traditional GM（ 1,1） model and the model is improved. It’sby using the constructed residual life prediction model of the corrosion pipelines and the optimized GM（ 1,1） model to calculate the remaining life of the corrosion pipelines that is the accuracy,accuracy,simple,feasible and pervasive method.